Case Report of Budd-Chiari Syndrome secondary to hepatic vein thrombosis: Case Report (Journal of Pharma Insights and Research, 2023)
Budd-Chiari syndrome is a rare disorder characterized by obstruction of hepatic venous outflow which can range from asymptomatic to severe manifestations including liver dysfunction. We present a case of a 29-year old male who presented with abdominal distension, breathlessness and dry cough. He had a history of Budd Chiari syndrome secondary to hepatic vein thrombosis for two years and portal vein thrombosis with cavernous transformation. Clinical examination revealed hepatomegaly and ascites. Laboratory investigations showed elevated liver enzymes and imaging revealed portal vein thrombosis with cavernous transformation. He was diagnosed with Budd-Chiari syndrome secondary to hepatic vein thrombosis. He underwent IVC venoplasty under fluoroscopy guidance using balloons with significant improvement seen post-procedure. Standard medical management including anticoagulation, antibiotics and supportive care was also provided. His liver function tests significantly improved after treatment. IVC venoplasty combined with medical management can be an effective treatment option for Budd-Chiari syndrome secondary to hepatic vein thrombosis.